REVIEW ON ROLE OF HERBAL DRUG IN THE PREVENTION AND MANAGEMENT OF KIDNEY DISEASE (AYUSHDHARA, 2016)
Kidney disease has always under concerned area since a long time specially in developing and under developing countries. It is one of the leading cause of death in world today. Incidence of kidney diseases leading to kidney failure is increasing day by day. The use of herbal drugs for the prevention and treatment of various diseases is now considered in thought throughout the world. A number of extracts of natural products have been reported to show protective effects against nephrotoxicity. Many herbal drugs have shown their potent nephroprotective effect due their antioxidant, diuretic, anti-inflammatory, antispasmodic properties. WHO has recently reported that traditional medicines have been existing in therapeutic practice even hundred years before the development of modern medicine. As herbs and herbal drugs have clinically proven effects like immunomodulation, adaptogenic and antimutagenic, they play a vital role in treatment of kidney diseases progressive to failure. Number of medicinal plants shows activity such as Punarnava &Varun reduces elevated blood urea & Serum Creatinine, Shigru & Sariva increase functional capacity like prevent renal injuries, helps improve haemopoiesis, Kasni restores electrolytic homeostasis like sodium and Pottasium, Revand Chini detoxify the effect like significantly reduces the deposition of 2,8-dihydroxyadenine content, Shigru acting as anti oxident, Shirish, Amalaki, Haritaki, Punarnava act as immunomodulator, Papaya, Coriandar reducing renal hypertention, Makoi, Purnarnava reduces oxidative stress. There are various evidences which revalidate the folklore use of traditional medicines and even be helpful in the development of future medicines, treatments and treatment guidelines of kidney disease.